2015
DOI: 10.5562/cca2764
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magnesium Doped Lithium Iron Silicate

Abstract: Abstract:The synthesis of Mg doped Li2Fe1-xMgxSiO4 (x = 0, 0.10 and 0.15) via solid-state reaction is reported. The product was characterized by Mössbauer spectroscopy (MS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), magnetic measurements and scanning electron microscopy (SEM). The structures of the reaction products were confirmed to be the monoclinic structure P21/n, but impurities were detected in them. In the undoped sample small amounts of lithium iron oxide or lithiated magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In addition, the binding energies of the Fe2 p , Li1s, O1 s , Si2 p for Ag 1+ , Zn 2+ , Cr 3+ , and Ti 4+ ‐doped samples (Figure B‐F) are very close to that of LFSO/C, which demonstrates that the metal ions doping does not change the oxidation state of Fe 2+ , Li 1+ , Si 4+ , and O 2− . Moreover the C 1 s XPS spectra originated a peak at 290 eV attributed to CO 3 2− which is evidence of the presence of Li 2 CO 3 , however, its intensity was found to be very small which indicated that the presence is only in trace amount . The atomic % of the dopant elements (Ag 1+ , Zn 2+ , Cr 3+ , and Ti 4+ ), that is present in the LFSO/C has been estimated by the XPS peak area calculation using the CASA XPS Software and tabulated in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the binding energies of the Fe2 p , Li1s, O1 s , Si2 p for Ag 1+ , Zn 2+ , Cr 3+ , and Ti 4+ ‐doped samples (Figure B‐F) are very close to that of LFSO/C, which demonstrates that the metal ions doping does not change the oxidation state of Fe 2+ , Li 1+ , Si 4+ , and O 2− . Moreover the C 1 s XPS spectra originated a peak at 290 eV attributed to CO 3 2− which is evidence of the presence of Li 2 CO 3 , however, its intensity was found to be very small which indicated that the presence is only in trace amount . The atomic % of the dopant elements (Ag 1+ , Zn 2+ , Cr 3+ , and Ti 4+ ), that is present in the LFSO/C has been estimated by the XPS peak area calculation using the CASA XPS Software and tabulated in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the C 1s XPS spectra originated a peak at 290 eV attributed to CO 3 2− which is evidence of the presence of Li 2 CO 3 , however, its intensity was found to be very small which indicated that the presence is only in trace amount. 23,24 The atomic % of the dopant elements (Ag 1+ , Zn 2+ , Cr 3+ , and Ti 4+ ), that is present in the LFSO/C has been estimated by the XPS peak area calculation using the CASA XPS Software and tabulated in Table 1. From Table 1, the estimated content of dopant elements Ag, Zn, Cr, and Ti at Fe site in the LFSO/C sample is 0.671, 1.170, 1.172, and 1.169 (at.%), respectively.…”
Section: Structural and Morphological Characterizationsmentioning
confidence: 99%
“…The same peak splits into two stronger bands, which indicates the orthorhombic structure of Li 2 NiSiO 4 [31,32]. The other characteristic absorption bands at 1455 cm −1 are assigned to the Li 2 CO 3 formed at the surface [33]. Figure 4 reveals the first charge and discharge capacity plateaus vs. the working voltage between 4.5 and 1.5 V at C/10.…”
Section: Resultsmentioning
confidence: 96%
“…The cobalt doped Li 2 FeSiO 4 /C cathode presented a discharge capacity of 142 mAh g −1 at a rate of 3 C even after 100 cycles which was better than an undoped sample [93] (Figure 4(ii)). Jaen et al [94] . and Yi et al [87] .…”
Section: Silicates: An Alternative Viable Cathode?mentioning
confidence: 99%
“…[92] The cobalt doped Li 2 FeSiO 4 /C cathode presented a discharge capacity of 142 mAh g À 1 at a rate of 3 C even after 100 cycles which was better than an undoped sample [93] (Figure 4(ii)). Jaen et al [94] and Yi et al [87] were reported the magnesium and manganese doping at the iron site could boost charge storage efficiency and good capacity retention over number of cycles. Recent work was noticed that Mn substitution at the Fe site of Li 2 Fe 0.8 Mn 0.2 SiO 4 /C had higher energy density (655 Wh.kg À 1 ) than undoped Li 2 FeSiO 4 /C (408 Wh.kg À 1 ).…”
Section: Fesio 4 Cathodes For Libsmentioning
confidence: 99%